2013
DOI: 10.1080/17429145.2013.774442
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic adaptation ofEuphorbia fractiflexa(Euphorbiaceae) and survival in arid regions of the Arabian Peninsula

Abstract: Arid regions of the Arabian Peninsula are characterized by a short wet season with erratic rainfall, high temperature, and high evaporation. In these arid regions, the leafless stem succulent Euphorbia fractiflexa S. Carter & J.R.I.Wood (Euphorbiaceae) is an abundant perennial. Work presented in this paper aimed at investigating crassulacean acid metabolism (CAM) as a physiological adaptation crucial for survival of E. fractiflexa in arid regions of the Arabian Peninsula. Work involved investigations of stomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This decrease in Φ PSII was attributed to an over-energized of PSII during phase III of CAM photosynthesis [ 38 ]. Likewise, the same behavior was observed in other CAMs [ 19 ] and succulent plants [ 20 ]. In no-succulent plants such as wheat and peach, Fv/Fm and ΦPSII were dramatically decreased at temperatures between 30°C and 45°C, while the F 0 values were greatly increased as result of a severe stress in which complex antenna disconnection and severe disintegration of PSII was observed [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This decrease in Φ PSII was attributed to an over-energized of PSII during phase III of CAM photosynthesis [ 38 ]. Likewise, the same behavior was observed in other CAMs [ 19 ] and succulent plants [ 20 ]. In no-succulent plants such as wheat and peach, Fv/Fm and ΦPSII were dramatically decreased at temperatures between 30°C and 45°C, while the F 0 values were greatly increased as result of a severe stress in which complex antenna disconnection and severe disintegration of PSII was observed [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, differences in photosynthetic efficiency determined from the parameters and ratios mentioned above can be used to detect physiological changes resulting from environmental conditions such as extreme temperatures [ 18 ]. For instance, in the obligate CAM Euphorbia fractiflexa , temperatures of 40°C in field induced a decrease of Fv/Fm and Φ PSII , suggesting that this response is given by the physiological adaptation to tolerate drastic environmental conditions [ 19 ]. Moreover, Musil et al (2009) [ 20 ] found that in southern African succulents growing to high temperatures (40–54°C), a decrement of the photosynthetic performance was the principal cause of massive mortalities of endemic desert plants.…”
Section: Introductionmentioning
confidence: 99%
“…Cactiform Euphorbia with ribbed stems, resemble "columnar cacti", and are often confused with the Cactaceae, but are identifiable by their twin spines carried on a spine shield and their ability to secrete a "milky sap" called latex in response to physical aggression (Chaudhary et al, 2023). Furthermore, these cactiforms adopt the CAM photosynthetic system (Edwards & Donoghue, 2006;Al-Turki et al, 2014;Niechayev et al, 2019). This photosynthetic regime specifically allows it to adapt to prolonged drought (Evans et al, 2014;Masrahi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%